Topological organization of CA3‐to‐CA1 excitation. (2nd July 2015) - Hongo, Yoshie; Ogawa, Koichi; Takahara, Yuji; Takasu, Keiko; Royer, Sebastien; Hasegawa, Minoru; Sakaguchi, Gaku; Ikegaya, Yuji
Abstract The CA1‐projecting axons of CA3 pyramidal cells, called Schaffer collaterals, constitute one of the major information flow routes in the hippocampal formation. Recent anatomical studies have revealed the non‐random structural connectivity between CA3 and CA1, but little is known regarding the functional connectivity (i.e. how CA3 network activity is functionally transmitted downstream to the CA1 network). Using functional multi‐neuron calcium imaging of rat hippocampal slices, we monitored the spatiotemporal patterns of spontaneous CA3 and CA1 burst activity under pharmacological GABAergic blockade. We found that spatially clustered CA3 activity patterns were transformed into layered CA1 activity sequences. Specifically, synchronized bursts initiated from multiple hot spots in CA3 ensembles, and CA1 neurons located deeper in the pyramidal cell layer were recruited during earlier phases of the burst events. The order of these sequential activations was maintained across the bursts, but the sequence velocity varied depending on the inter‐burst intervals. Thus, CA3 axons innervate CA1 neurons in a highly topographical fashion.